Effect of iron and zinc supplementation in the treatment of malaria in children - Danny Dasraf; Bugis Mardina Lubis; Bidasari Lubis; Nelly Rosdiana; Munar Lubis; Syahril Pasaribu (Indonesian Pediatric Society, 2007)
Background Iron and zinc administration for children withmalaria in endemic area were known to decrease parasitemia butdata on their effectiveness when given together to increasereticulocytes as erythropoiesis parameter and hemoglobin isinsufficient.Objective To determine the effect of zinc to increase ironabsorption in the treatment of Plasmodium falciparum malaria inchildren.Methods Children with positive Plasmodium falciparum on theirblood smear (n=86) examination were randomly assigned to dailysupplementation of iron 6 mg per kg body weight per day plusplacebo or iron plus zinc 10 mg per day for 30 days. Venous bloodspecimens were collected at the start and at the end of the study.Results Sixty-nine children completed the supplementations andhad both baseline and follow-up blood specimen study. After 30-day supplementation, the iron plus placebo and iron plus zincgroups showed significant difference on hemoglobin concentration(0.58 and 0.09 g/dl; P<0.05). There was no significant differencein reticulocyte production index and reticulocyte count beforeand after intervention in both groups. There was only significantdifference in red blood cells concentration after supplementationof iron plus placebo and iron plus zinc (4.7 in 4.5 million/Î¼l;P<0.05).Conclusions Iron supplementation with or without zinc showssignificant increase of hemoglobin concentration. It is slightlyhigher in iron plus placebo group.